Silica-collagen bionanocomposites as three-dimensional scaffolds for fibroblast immobilization - Desimone, Martín Federico (2010)
Silica-collagen bionanocomposite hydrogels were obtained by addition of silica nanoparticles to a protein suspension followed by neutralization. Electron microscopy studies indicated that larger silica nanoparticles (80 nm) do not interact strongly with collagen, whereas smaller ones (12 nm) form rosaries along the protein fibers. However, the composite network structurally evolved with time due to the contraction of the cells and the dissolution of the silica nanoparticles. When compared to classical collagen hydrogels, these bionanocomposite materials showed lower surface contraction in the short term (1 week) and higher viability of entrapped cells in the long term (3 weeks). A low level of gelatinase MMP2 enzyme expression was also found after this period. Several proteins involved in the catabolic and anabolic activity of the cells could also be observed by immunodetection techniques. All these data suggest that the bionanocomposite matrices constitute a suitable environment for fibroblast adhesion, proliferation and biological activity and therefore constitute an original three-dimensional environment for in vitro cell culture and in vivo applications, in particular as biological dressings.